Perceptions of Contextual Stressors in Physical Education. A Qualitative Case Study - Åsebø, Eli-Karin Sjåstad; Løvoll, Helga S.; Krumsvik, Rune Johan (Frontiers in Sports and Active Living, 2020)
Background: Daily stressors have a significant impact on students’ educational outcomes. However, research on students perceived and common contextual stressors in physical education (PE) lessons is limited. Purpose: To identify potential contextual stressors in PE contexts and what students perceive as stressors. Participants: Ninth-grade students and their PE teachers recruited from three classes in one lower secondary school in Norway. Research design: This qualitative case study used data generated from descriptive field notes from participant observations in PE lessons, formal interviews and informal conversations with PE teachers, focus group and individual interviews with students, and a supplementary survey using the TurningPoint student response system. Conversations were transcribed verbatim and analyzed using reflexive thematic analysis (1–3) and the NVivo 12 Pro analysis software. The survey was analyzed using IBM SPSS Statistics 21. Findings: This study supports and expands previous research exploring students’ stressors in PE and highlights the volume and variety of potential stressors in PE contexts. The findings shed light on certain similarities and differences that may exist between students of different genders and grades and with different past physical activity experiences. In the present study, spectators, in addition to difficult tasks and low self-efficacy, seemed particularly stressful for girls. This article presents nuances revealed by various qualitative approaches and a supplementary survey. Conclusion: Students in this study experience a multitude of stressors during PE lessons. These include stressors in the teaching, physical, and social environments, as well as personal factors. The stressors experienced depend on the situation, the lesson content, the parties involved, students’ past experiences, and their appraisal of these stressors. In our sample, girls seemed to be more vulnerable to contextual stressors in PE than boys.